2018
DOI: 10.1111/dmcn.13774
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic motion abnormalities and bimanual performance in children with unilateral cerebral palsy

Abstract: Children with unilateral cerebral palsy had more movement deviations than typically developing children in unimanual tasks. A strong relationship was found between movement deviations of the impaired upper limb and bimanual performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 25 publications
3
19
0
1
Order By: Relevance
“…In this context, our results reinforce the findings of Gaillard et al,52 who noted that in individuals with CP, kinematic abnormalities were more pronounced in the distal segments (elbow flexion–extension, pronosupination, and wrist flexion–extension). The authors indicated that this finding may be related to muscle weakness and to increased muscle tone being more prominent distally and having a higher influence on distal movements.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this context, our results reinforce the findings of Gaillard et al,52 who noted that in individuals with CP, kinematic abnormalities were more pronounced in the distal segments (elbow flexion–extension, pronosupination, and wrist flexion–extension). The authors indicated that this finding may be related to muscle weakness and to increased muscle tone being more prominent distally and having a higher influence on distal movements.…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, for the required movement using a webcam, the CP individuals only had to wave their hands in front of the camera in the correct places to achieve the task, which requires more velocity than fine movements and coordination, corroborating the findings of Fernani et al50 Thus, this better functionality in velocity and overall movements may have been responsible for the best performance in the MoveHero task 50. In this sense, it should be noted that such findings reinforce what has been reported in the literature, which indicates that the execution of overall movements is easier to perform when compared with the execution of finer movements in individuals with CP 5052…”
Section: Discussionsupporting
confidence: 82%
“…Using three-dimensional movement analysis in children with unilateral CP, Gaillard et al 1 showed that deviations from typical movement trajectories in the moreaffected upper limb (particularly in distal segments) are related to the performance of the more-affected hand in bimanual tasks as measured using the Assisting Hand Assessment (AHA). Using three-dimensional movement analysis in children with unilateral CP, Gaillard et al 1 showed that deviations from typical movement trajectories in the moreaffected upper limb (particularly in distal segments) are related to the performance of the more-affected hand in bimanual tasks as measured using the Assisting Hand Assessment (AHA).…”
mentioning
confidence: 99%
“…One starts by considering to what extent performance in unimanual and bimanual tasks is limited by biomechanical constraints and neurological control of the more-affected limb. Using three-dimensional movement analysis in children with unilateral CP, Gaillard et al 1 showed that deviations from typical movement trajectories in the moreaffected upper limb (particularly in distal segments) are related to the performance of the more-affected hand in bimanual tasks as measured using the Assisting Hand Assessment (AHA). This is a highly plausible finding.…”
mentioning
confidence: 99%
See 1 more Smart Citation